Prediction of the Site of Coronary Artery Lesion in Acute Inferior Myocardial Infarction with Right Sided Precordial Lead (V4r) - Alam, MS; Ullah, M; Ulabbi, SU; Haque, MM; Uddin, R; Mamun, MS; Majumder, AAS (Cardiovascular Journal, 2012)
Background: The patient with inferior wall AMI, site of culprit lesions is an important determinant of outcome. Patient with RV infarction have a poor prognosis whereas those with occlusion of LCX have a good prognosis. Early diagnosis and treatment substantially reduce cardiac events particularly in high-risk patients. V4R can be used as to locate the site of obstruction. Materials and methods: 81 patients with acute inferior myocardial infarction admitted to the coronary care unit (CCU) within 12 hours after the onset of chest pain who underwent coronary angiogram were included in the study. Standard 12-lead ECG with right precordial lead V4R was recorded. Patients were categorized into within 3 groups according to early changes of V4R-Group- I - ST-segment elevation > 1 mm and positive T- wave, Group-II- ST-segment iso-electric and positive T-wave, Group-III- ST-segment depression >1 mm and negative T -wave. Results: In group I patients, highest percentage of the patients had lesion in proximal RCA (97.2%); whereas in group II patients, highest percentage in the distal RCA (89.7%) followed by LCX (41.4%) and in group III patients, highest percentage also in LCX (100.0%) followed by LAD (56.3%). Based on analysis of sensitivity and specificity, it was revealed that in group I patients of ECG finding suggested 100.0% sensitivity, 97.8% specificity and 98.8% accuracy. In group II patients, 92.9% sensitivity, 94.3% specificity and 93.8% had accuracy. In case of group III patients, 93.8% sensitivity, 98.5% specificity and 97.5% accuracy. Conclusion: The configuration of the ST-T segment in lead V4R is a sensitive and specific tool to recognize the occluded vessel in acute inferior MI whether it is proximal RCA, distal RCA or LCX. Since it is an inexpensive method, it can be readily used to locate the site of occlusion in AMI - Inferior. Keywords: Coronary artery disease; Myocardial infarction;, Lead V4r. DOI: http://dx.doi.org/10.3329/cardio.v4i1.9389 Cardiovasc. J. 2011; 4(1): 46-52